PENGARUH SUSTAINABILITY REPORTING DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2022-2025) - Nadya Putri Wijaya; Puji Astuti; Hestin Sri Widiawati (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Sustainability issues have become increasingly important in corporate decision-making, particularly in the mining sector, where business activities generate substantial environmental and social impacts. Consequently, sustainability reporting has emerged as a strategic communication tool that may influence investors' perceptions of firm value. In addition to sustainability disclosure, firm size is also considered an important determinant of firm value, while profitability is expected to strengthen or weaken these relationships. This study aims to examine the effects of sustainability reporting and firm size on firm value, with profitability serving as a moderating variable. A quantitative research approach was employed using Moderated Regression Analysis (MRA). The research sample consisted of 18 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period, resulting in 72 firm-year observations selected through purposive sampling. Secondary data were collected from annual reports and sustainability reports published by the companies and the IDX. The findings reveal that sustainability reporting has no significant effect on firm value, whereas firm size has a significant negative effect and profitability has a significant positive effect on firm value. Furthermore, profitability does not moderate the relationship between sustainability reporting and firm value or between firm size and firm value. Simultaneously, sustainability reporting, firm size, and profitability significantly influence firm value. These findings suggest that investors in the Indonesian mining sector continue to place greater emphasis on financial performance than on sustainability disclosure or firm size when evaluating corporate value.